Sociocultural threats in the state discourse of Imperial, Soviet and post-Soviet Russia: Strategies of representation - O.V. Vorobieva; F.V. Nikolai (Ученые записки Казанского университета: Серия Гуманитарные науки, 2021)
This article provides a comparative analysis of ideas about sociocultural threats in the official state documents dating back to the Imperial, Soviet, and post-Soviet periods of Russian history. The rhetorical construction of threats as part of the security discourse was considered. It was proved that the concept of threat is structured by the appropriate frame and includes figures of the bearer of the threat (agent), the object of the threat (patient), and a certain vision of the strategy of countering the threat (counteragent). The conclusion was made about the cyclical alternation of internal and external threats in the social and political thought of Russia. The priority of internal and external state threats over personal ones, the recognition of the state as a key historical agent was a stable trend of the Soviet and post-Soviet periods. In the first place throughout all the three periods was the threat to national security and territorial integrity, which is closely linked with the threat of lagging behind the West. The third place on this list was occupied by the threat of social and sociocultural split. The differences in the rhetoric of each period can be attributed to the changes in the macro-political situation. However, the general continuity of the structure of representation of threats, the unity of the thesaurus, and the priority of the state as a political actor remained with minimal changes.